Analisis Faktor-Faktor yang Berpengaruh terhadap Cash Holding pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2021 - Kelly Cherie; Hamaya Joya; Jaqceline Valencia Lee (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to test and analyze the factors affecting cash holding in the manufacturing industry listed on the Indonesia Stock Exchange from 2018 to 2021. Factors considered in this study include profitability, leverage, and liquidity. The population used in this study is the manufacturing industry and listed on the Indonesia Stock Exchange (IDX) with a total sample of 67 samples using the purposive sampling method. Multiple linear regression analysis is used via SmartPLS 3. The test results on the profitability variable show that the profitability variable has a negative effect on cash holding. Companies with high profits, then companies will tend to use their cash balances to develop business, add assets, meet investment opportunities, so that funds are not included in cash holding funds. Test results on variable leverage show that variable leverage negatively affects cash holding. Cash ownership is inversely proportional to leverage, so the relationship between these variables is negative because if internal funds are not enough, the company will use its liquid reserves, namely cash holding, before issuing debt. The test results on the liquidity variable show that the liquidity variable has a positive effect on cash holding. In line with the results of research which states that liquidity has a positive effect on cash holding. The findings of this study can be useful for policymakers, investors, and managers in formulating strategies to optimize cash holding in the manufacturing industry.